Quantum-Chemical Study For Some β-Lactam Drevatives by using Hyper Chem Calculations - Zainab Y. Kadhim (Journal of Global Pharma Technology, 2018)
In the present research, we studied the properties of three β-lactam derivatives(C18H12N2OS3 , C25H17FN2O3S and C22H19ClN2O5S2). The study was carried out by using semi-empirical methods (ZINDO/1, ZINDO/S, and PM3), to identify the binding energy ∆Eb, heat effect of ∆Hof formation, and dipole moment for some β-lactam derivatives. Inaddtion, the electronic transitions and vibration modes were computed for these compounds. HOMO and LUMO energies were calculated to determine the reactive sites of these compounds.Keywords: β-lactam, Semi-empirical methods, Heat the formation.